Widening how we see the impact of culture on learning, practice and identity development in clinical environments. Issue 1 (2nd September 2021) - Sheehan, Dale; Wilkinson, Tim J.
Abstract: As part of this State of the Science series on Self, Society and Situation, we focus on how we might see the situation of the workplace as a learning environment in the future. Research to date into how health professionals learn while working in clinical workplace environments has mostly focused on the supervisor‐trainee relationship or on the interaction between the affordances of a workplace and the receptiveness of trainees. However, the wider environment has not received as much focus—though frequently mentioned, it is seldom investigated. We suggest there is a need to embrace the wider institution factors, recognise and acknowledge an organisation's values and culture as they impact on clinical learning in order to work with these, not around them or ignore them, to make what may be tacit visible through reflection and observation and to embrace a range of perspectives on culture. Abstract : Sheehan and Wilkinson focus on how learning is shaped by the physical environment, the interactions and behaviours of other health professionals, the systems in place to guide care, and culture to challenge beliefs about who 'holds' knowledge.